On the ecological preferences of Dactylorhiza fuchsii (Druce) Soo` in the north-east of the Kirov region - Egorova , N. Yu.; Suleimanova V. N, V. N.; Yaroslavtsev, A. V. (Проблемы ботаники Южной Сибири и Монголии, 2021)
Dactylorhiza fuchsii (Druce) Soo’– summer-green tuber-forming polycarpic. As a result of the conductedstudies, it was found that in relation to the complex of all ecological scales, D. fuchsii belongs to mesobiont species, withthe manifestation of stenovalence in the variability of moisture and salt regime of soils. It is revealed that the main factorslimiting the distribution of the species within the considered fragment of the range are the richness of soils with nitrogenand illumination.